Determinación del momento óptimo de la inseminación artificial con la observación de células cornificadas del epitelio vaginal en hembras bovina de la Universidad Técnica de Babahoyo - Peñafiel Guillén, Byron Willyn (2016)
SUMMARY In Ecuador, the artificial insemination technique in bovine is used by farmers; however, the low efficiency causes fewer pregnant animals annually, resulting in low production of milk and meat. This study aimed to determine the morphological changes of vaginal epithelium cells as an indicator of the exact time for artificial insemination and define a practical method for determining the optimum time for artificial insemination in bovine females. In the livestock area of the Universidad Técnica de Babahoyo, during a period of 120 days, a study using 17 females cattle was performed, using as factors variables as: cytology of vaginal epithelial cells, signs and symptoms of estrus and pregnancy rates after artificial insemination and / or natural service. This in order determine the method for identifying the optimal timing of artificial insemination based on the percentage of cornified vaginal epithelial cells in bovine females. Using a compound microscope, the evaluation of the slides containing the vaginal smear was performed, allowing to evaluate the presents cells and categorizing it as parabasal, intermediate early, middle, late intermediate, and cornified / keratinized; so it was considered the highest percentage of cornified vaginal epithelial cells for the optimal timing of artificial insemination and / or natural service. The results indicated that the smear technique was very clear in showing the stages of vaginal epithelial cells throughout the period of estrus in bovine females. Also, considering the cornified cells present in high percentages, it is possible to obtain up to 30% pregnancy rate. The presence of cornified cells> 40% combined with a high percentage of late intermediate cells> 30% and the body reflexes confinement with breeding bull 100% pregnancy rate is achieved. The presence of visual signs are not only indicators for determining the period of estrus, since when were considered for artificial insemination and / or mounted; females were diagnosed not pregnant. Due to the irregularity of the recorded data with respect to the fluctuation of the percentage of vaginal epithelial cells, probably caused by the body condition of the animals, it is recommended to establish new studies using females with good body condition.